Health and labor markets - Polachek, Solomon W.; Tatsiramos, Konstantinos (Research in labor economics ;, 2019)
A country's economic productivity is directly related to the health of its workforce. Thus, how a nation allocates resources to the physical health of its population is of vital importance in establishing the economic well-being of its citizens.This volume contains nine original and innovative articles that investigate the relationship between a nation's health policies, employee health and resulting labor market outcomes. Topics include the direct link between employees' health and wages, the employment impact of an unfavorable health shock, the relationship between job insecurity and a worker's mental health, the effect of career disruptions on already chronically ill workers, the consequences of arbitrary health insurance disenrollments, the impact of reducing publically available sick day benefits, the repercussions of increasing employers' sick pay benefits on absenteeism, the relationship between economic conditions and opioid abuse, and the consequences of parental migration on children's health.For researchers and students of labor economics, or anyone interested in understanding how a country's health policies affect its economic productivity, this volume is a fundamental text.